2017
DOI: 10.1007/s11999-016-4740-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain Control and Functional Milestones in Total Knee Arthroplasty: Liposomal Bupivacaine versus Femoral Nerve Block

Abstract: Background Although pain management after total knee arthroplasty (TKA) affects rehabilitation, length of stay, and functional outcomes, pain management for patients undergoing TKA has yet to be standardized. Femoral nerve blocks (FNBs) are commonly used as an adjunct; however, these can result in transient quadriceps weakness and have been associated with in-hospital falls. Periarticular infiltration of liposomal bupivacaine has been recently introduced as a long-acting analgesic that can be administered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Only 1 study refers to the proper random sequence generation [24] and 6 studies were all referred to unknown risk of bias. [1924,26] The study of Yu et al [25] is with high risk of bias for the random sequence generation. [25] The overall kappa value regarding the evaluation of risk of bias of included RCTs was 0.736, indicating an excellent degree of agreement between the 2 reviewers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 1 study refers to the proper random sequence generation [24] and 6 studies were all referred to unknown risk of bias. [1924,26] The study of Yu et al [25] is with high risk of bias for the random sequence generation. [25] The overall kappa value regarding the evaluation of risk of bias of included RCTs was 0.736, indicating an excellent degree of agreement between the 2 reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [19,21,2325] with 1653 patients were used to carry out a meta-analysis on the VAS at 48 hours and final results revealed that there was no significant difference between VAS at 48 hours (MD = −4.16; 95% CI −8.76–0.43; P  = 0.076, Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ketamine has been reported to be more efficient when combined with bupivacaine and a femoral nerve block (19). Bupivacaine is recommended for treating post-operative pain management following TKA, as it induces fewer adverse effects and does not affect any motor function (4,20). Previously, Inanoglu et al (21) concluded that ketamine and bupivacaine (multimodal regimen) could effectively control the post-operative pain following tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, femoral nerve blockade has been the preferred strategy for pain management after TKA surgery in many centers around the world, and has been shown to be superior to morphine patient-controlled analgesia and equivalent to epidural pain management [4,22]. More recently, it was reported that PAI might be better than continuous femoral nerve block in terms of pain relief after TKA in retrospective [17,23] and prospective trials [12,19], and might even improve the time for discharge from the hospital [9]. One recent meta-analysis of 14 randomized controlled trials confirmed that femoral nerve block was not superior to PAI in terms of opioid consumption, pain scores (at rest or movement), ROM, muscle strength and length of stay [1].…”
mentioning
confidence: 99%